GAMBARAN PERANAN PENYULUHAN METODE DEMONSTRASI TERHADAP PENGETAHUAN MENYIKAT GIGI PADA SISWA/I KELAS IV SD 068003 KAYU MANIS PERUMNAS SIMALINGKAR KECAMATAN MEDAN TUNTUNGAN - Sri Junita Nainggolan (Poltekkes Kemenkes Medan, 2017)
Brushing teeth is one of the methods to maintain dental hygiene and oral health. It can ward off the incidence of caries. In general, dental and oral health education is obtained from counseling. The group of people that usually becomes the target is elementary school children because the age of 6-14 years is a transition period or the change in permanent teeth (mixed teeth period).In this research, the counseling was the one with demonstration method which was aimed to increase the knowledge of brushing teeth in Grade IV students at SD 068003 Kayu Manis, Perumnas Simalingkar, Medan Tuntungan Subdistrict with 30 students as the samples.The result of the research showed that before the counseling, 18 respondents (60%) were in good criteria in their knowledge of brushing teeth correctly and 11 respondents (36.7%) were in moderate category. After the counseling with demonstration method, all respondents (100%) were in good category.The conclusion was that counseling with demonstration method could improve students’ knowledge of brushing teeth. It is recommended that Grade IV students at SD 068003 brush their teeth properly and correctly.